IMPLEMENTASI APLIKASI RPG MAKER VX ACE SEBAGAI SARANA GAME EDUKASI TIGA RAGAM BAHASA DI SMP NEGERI 2 PURBALINGGA - Nugroho, Lustiyono Prasetyo; Imron, Mohammad (Jurnal Sistem Informasi Kaputama (JSIK), 2021)
School is a place for teaching and learning activities that are being carried out by each teacher to students, including theoretical and practical reviews. In the learning process the teacher is recommended to provide good quality teaching and learning activities, and to further refine these activities, a new media is needed in the learning process. Because based on the results of interviews with several teachers, it can be concluded that in the learning process students are less motivated, especially in the extra hours or evening hours and the lack of interaction makes students respond less and less. For this reason, in an effort to realize the quality of learning, new learning media are created that educate students such as educational games, where students can experience learning while playing. This can be used as a modern example, especially in the learning process of SMP Negeri 2 Purbalingga students. In accordance with the description above, this research takes the title "IMPLEMENTATION OF THE RPG MAKER VX ACE APPLICATION AS A THREE DIVERSE LANGUAGE EDUCATIONAL GAME MODELS IN SMP NEGERI 2 PURBALINGGA". The purpose of this study was to develop educational game learning media with 3 different languages to help teachers deliver material in the classroom and increase the motivation of students. So that later it can trigger interactions between teachers and students. With the hope that students will be able to understand the material presented by the teacher through the educational game, because based on the assessment of the student questionnaire, the educational game application results in an average index of 88.26% and a teacher representative questionnaire of 94.99%. So it can be concluded that this application is feasible to use and shows that this educational game learning media is very useful for use by students of SMP Negeri 2 Purbalingga.